Pulsating population: the rhythmicity of municipalities in the Czech Republic based on mobile phone location data - Adam Stražovec; Martin Erlebach; Marián Halás (Journal of Maps)
The daily, weekly, and seasonal rhythms of spatial units are based on spatial interactions, namely regular and irregular movements of people in space and time. This paper aims to identify different types of daily and weekly municipality rhythms using data from the Czech Republic obtained with mobile phone location data. Our research is based on changes in the concentration of people in these municipalities over the model week’s 168 h. An important part of the paper is the visualization of the results through structured weekly rhythm curves and final choropleth maps. The results show that diurnal rhythms (day vs. night during weekdays) are primarily conditioned by job and educational opportunities. The spatial distribution of municipalities according to these rhythms resembles a mosaic pattern. In contrast, the weekly rhythms (weekday vs. weekend) are more influenced by natural conditions (topography, relief, watersheds) and their resulting depiction on the map is mostly areal.